IDENTIFICATION CLASSIFICATION MEDICAL TERMINOLOGY DIAGNOSIS CODEFICATION UNDERLYING CAUSED OF DEATH AT RESPIRA LUNG HOSPITAL BANTUL YOGYAKARTA - setiyawan, hery; Zona Putra, Resdika; Rahmatullah, Widia (Jurnal Kesehatan Saintika Meditory, 2024)
Hospitals are health service facilities for the community with their own characteristics which are influenced by developments in health science, technological advances and the socio-economic life of the community which must continue to be able to improve services that are of higher quality and affordable for the community in order to achieve a higher level of health. Medical terminology is a system used to organize a list of medical terms for diseases, symptoms and procedures. Terms for diseases or health conditions must be in accordance with the terms used in a disease classification system. Coding activities are assigning codes using letters and numbers or a combination of letters and numbers that represent data components. Coding includes the activities of coding disease diagnosis and coding medical actions. Basic cause of death codes are very important for hospitals because they can influence hospital mortality reports and affect the validation and accuracy of information on the top 10 causes of death. Therefore, the underlying cause of death (UCoD) code must be filled in correctly and accurately to prevent errors in hospital reports and preventive measures. To select the basic cause is to determine the correct initial cause that precedes it on the bottom line in section I of the certificate by applying General Principles or selection rules rules 1, 2, and 3. The aim of the research is to identify the classification of medical terminology for coding diagnoses and the accuracy of coding diagnoses for the respiratory system at the Respira pulmonary hospital, Bantul, Yogyakarta. The research method is descriptive qualitative, with a case study research design, sampling technique using saturated sampling of death medical record files for June 2023-June 2024, a total of 22 mortality medical record files. Results and conclusions based on identification of classification of medical terminology, coding of diagnosis at the Respira Bantul pulmonary hospital, data on underlying causes of death (UCoD) were obtained based on ICD-10 chapters J18-J79, chapters A15-A19, chapters I60-I69, chapters D37-D48, chapter E10 -E14, chapters N17-N19, chapters R00-R09, R70-R79, chapters Z00-Z13. Classification of medical terminology and diagnosis codefication in ICD-10 Sepsis, Respiratory Failure, Chronic obstructive Pulmonary diseases, Neoplasms of the bronchus/lung, Respiratory failure, Suspect interstitial Lung Disease, Neoplasm of the bronchus/lung, Cerebral infraction, Estatic Bronchis, Neoplasm of the bronchus/Lung and I63 .9 ,J47, Z03.8, I21.3. R73.9 ,A16.2, E14.9, R04.2,J90, D38.1, N17.9, E79.0, R74.0, J81,D38.1, J96.9, R57.2.